The prevalence of secretor status and co-expression of lewis antigen in voluntary blood donors - Bharath, R Raj; Arumugam, P (Asian Journal of Medical Sciences, 2016)
Background: Blood group substances are present in soluble form in a majority of individuals in secretion such as saliva and body fl uids. Secretor status refers to the presence (SeSe and Sese) or absence (sese) of secretor gene which secrete ABH soluble substances. Secretor status can be used to resolve ABO discrepancies of people whose blood group cannot be identified by routine blood grouping and it can also help in identifying patients who may be a high risk group for getting certain diseases. Aims and Objectives: Our aim and objectives of the study is to fi nd out the Prevalence of Secretor Status and Co-expression of Lewis Antigens among the Voluntary Blood Donors. Materials and Methods: This study was conducted in sixty volunteers and the method used to determine the secretor status was hemagglutination inhibition method. Their blood was used to detect the type of Lewis (Le) antigen since the type of Lewis antigen correlated with the secretor status of the individual. Results: Among the sixty subjects tested, forty fi ve of them were found to be secretors and fifteen of them were Non-secretors. The number of Lewis (a+b-) individuals were twelve, Lewis (a-b+) were thirty nine and Lewis (a-b-) were nine. Conclusion: The prevalence of secretors was 75% and non-secretors were 25% respectively. We found 65 % of the volunteers were found to be Le (a-b+) positive, 20% were Le (a+b-) and the remaining 15% were Le (a-b-) which correlated with the ABH antigen secretor status. Asian Journal of Medical Sciences Vol.7(5) 2016 93-96